2017
DOI: 10.1016/j.nima.2017.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Beam tuning and bunch length measurement in the bunch compression operation at the cERL

Abstract: Realization of a short bunch beam by manipulating the longitudinal phase space distribution with a finite longitudinal dispersion following an off-crest acceleration is a widely used technique. The technique was applied in a compact test accelerator of an energy-recovery linac scheme for compressing the bunch length at the return loop. A diagnostic system utilizing coherent transition radiation was developed for the beam tuning and for estimating the bunch length. By scanning the beam parameters, we experiment… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…We also confirmed that the achromat condition was retained while the R 56 knobs were being changed. From the symmetric design of the arc, the transverse dispersion at the center of the arc η c and the R 56 of the arc are related by R 56 = 1.414η c − 0.34 [m], in the present case [45]. By measuring η c , the R 56 of the arc can be estimated indirectly.…”
Section: Application Demonstration Setupmentioning
confidence: 96%
See 1 more Smart Citation
“…We also confirmed that the achromat condition was retained while the R 56 knobs were being changed. From the symmetric design of the arc, the transverse dispersion at the center of the arc η c and the R 56 of the arc are related by R 56 = 1.414η c − 0.34 [m], in the present case [45]. By measuring η c , the R 56 of the arc can be estimated indirectly.…”
Section: Application Demonstration Setupmentioning
confidence: 96%
“…We used coherent radiation as an indirect tool to evaluate the bunch length. A terahertz interferometer system using coherent transition radiation (CTR) was developed approximately 10 m upstream of the FEL undulator in the same straight section [45]. By detecting the autocorrelation with a Michelson interferometer, the spectrum of the bunch can be obtained.…”
Section: Application Demonstration Setupmentioning
confidence: 99%
“…Other well-known techniques to perform bunch length measurements are: (i) the streak camera: a high time resolution camera (based on the use of a photo-multiplier and a rapidly changing electric field) collects the light from a specific screen (e.g. an Optical Transition Radiation screen) which produces a light pulse of the same length as the electron bunch 20 ; (ii) Electro-Optical Sampling (EOS), which uses an external laser that passes through a non linear crystal parallel to the beam, to measure the polarization modulation on the laser pulse due to the electric field associated with the bunch 21 , 22 ; (iii) spectral analysis of the bunch frequency content; the bunch length is assessed by analyzing the frequency spectrum of coherent emission from the bunch 23 27 , and (iv) the measurement of the beam energy spread when using an accelerating cavity not on the RF crest 28 – 30 .…”
Section: Introductionmentioning
confidence: 99%